2014
DOI: 10.15662/ijareeie.2014.0307006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Load Flow Algorithm for Multi-Phase Balanced/ Unbalanced Radial Distribution Systems

Abstract: ABSTRACT:In this work, distribution system load flow analysis is formulated and tested for fundamental steady-state and harmonics power flow. For the steady-state analysis, a novel power flow formulation method for the general multiphase balanced and/or unbalanced radial distribution systems is presented. The special topology of the power distribution system has been fully exploited to facilitate obtaining a direct solution using the graph theory. Only one developed matrix used in conjunction with simple stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…after reconfiguration). Accordingly, it can be concluded that the proposed MICP model is more efficient than approach presented in [90] and faster than GA.…”
Section: B Case 2: 12-bus Distribution Networkmentioning
confidence: 82%
See 4 more Smart Citations
“…after reconfiguration). Accordingly, it can be concluded that the proposed MICP model is more efficient than approach presented in [90] and faster than GA.…”
Section: B Case 2: 12-bus Distribution Networkmentioning
confidence: 82%
“…Moreover, Fig. 7 and 8 show that the system voltage is improved considerably after reconfiguration by the proposed model compared to the base case and the model presented in [90] (e.g. the minimum voltage of the system at bus 7 has been increased from 0.9966 p.u.…”
Section: B Case 2: 12-bus Distribution Networkmentioning
confidence: 88%
See 3 more Smart Citations